Metoda robnih elementov v akustiki - primer ovrednotenja zvočnega polja enosmernega elektromotorja - Furlan, Martin (Strojniški vestnik, 2004)
This paper presents a basic approach to solving exterior acoustic problems using the boundary-element method (BEM) and the development of a BEM program for solving three-dimensional (3D) problems. It also shows the integration of the developed BEM program into a finite-element method (FEM) program, which isprimarily used to evaluate the structural response that generates a sound field, but can also be used to pre-process and post-process the acoustic model. The program was verified by using an acoustic problem for which the analytical solution was already known. The verification was performed by researching the influence of the discretization density on the accuracy of thenumerically defined sound field. In addition to this, we also evaluated thetime necessary to solve the problem and its system of linear equations, andrelated it to the method chosen for solving this system of linear equations. The program was applied to a real case where the sound field of a DC electric motor was calculated using the BEM. Based on the structural response of the DC electric motor that is the result of the harmonic excitation of magnetic forces, and was calculated with the FEM, we evaluated the sound field surrounding the DC electric motor.
Keywords: akustika; metode robnih elementov; hrup; dinamika struktur; metoda robnih elementov; zvočno polje